2022
DOI: 10.1186/s13690-022-00952-w
|View full text |Cite
|
Sign up to set email alerts
|

Telerehabilitation for upper limb disabilities: a scoping review on functions, outcomes, and evaluation methods

Abstract: Background Upper limb (UL) disabilities have attracted worldwide attention due to the high economic costs of health care and the negative effects on the quality of life of patients with these disabilities. Telerehabilitation technologies are one of the most important ways to reduce rehabilitation costs and increase the quality of life of patients. Therefore, the aim of this study was to investigate the role of telerehabilitation in improving the health status of patients with upper limb disabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 105 publications
3
15
0
Order By: Relevance
“…As discussed above, telerehabilitation and virtual reality were two types of technology used along with rehabilitation robots. Some studies [ 3 , 82 , 83 ] showed that if special interventions such as game-based virtual reality, and telerehabilitation with rehabilitation robots are used, upper limb function, mental health and patients’ participation in rehabilitation exercises can be improved. Moulaei et al [ 3 ], showed in a scoping review that telerehabilitation could lead to “improving in musculoskeletal functions”, “increasing patients’ interest and motivation to perform rehabilitation exercises”, “increasing adherence to rehabilitation exercises and more participation in treatment processes”, “remote monitoring and control of patients”, “reducing or relieved pain” and “improving quality of life”.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As discussed above, telerehabilitation and virtual reality were two types of technology used along with rehabilitation robots. Some studies [ 3 , 82 , 83 ] showed that if special interventions such as game-based virtual reality, and telerehabilitation with rehabilitation robots are used, upper limb function, mental health and patients’ participation in rehabilitation exercises can be improved. Moulaei et al [ 3 ], showed in a scoping review that telerehabilitation could lead to “improving in musculoskeletal functions”, “increasing patients’ interest and motivation to perform rehabilitation exercises”, “increasing adherence to rehabilitation exercises and more participation in treatment processes”, “remote monitoring and control of patients”, “reducing or relieved pain” and “improving quality of life”.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies [ 3 , 82 , 83 ] showed that if special interventions such as game-based virtual reality, and telerehabilitation with rehabilitation robots are used, upper limb function, mental health and patients’ participation in rehabilitation exercises can be improved. Moulaei et al [ 3 ], showed in a scoping review that telerehabilitation could lead to “improving in musculoskeletal functions”, “increasing patients’ interest and motivation to perform rehabilitation exercises”, “increasing adherence to rehabilitation exercises and more participation in treatment processes”, “remote monitoring and control of patients”, “reducing or relieved pain” and “improving quality of life”. Fernández-Vázquez et al [ 84 ], also pointed out that virtual reality as a very interesting tool in treating upper limb disorders along with rehabilitation robots can improve the motor function of the upper limb, increase users’ motivation and enjoyment, a large number of repetitions or high intensity rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…64,65 Likewise, if the games are combined with telerehabilitation technologies, robots and/or smart wearables, they can increase the motivation and tendency of patients to perform therapeutic exercises, easily perform repetitive, boring and longterm exercises, increase the patient's independence in performing therapeutic exercises, increasing adherence to rehabilitation exercises and ultimately improving the quality of life of patients with upper limb disability. 2 Other outcomes identified in this review were "High user satisfaction with the system," and "Increasing patients' autonomy in daily life activities." Some studies [66][67][68] have shown that rehabilitation games are useful and effective for people with upper limb disabilities, and these individuals and therapists have also reported a high level of satisfaction and acceptance of these games.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the technology allows more intensive and tailored patient rehabilitation activities and services (increasing the amount and quality of therapy that can be administered and supervised) and enable all the involved actors in the team (e.g., physicians, therapists, bioengineers and others) to design patient-centered and custom intervention collaboratively. Moreover, technology can transform rehabilitation from a one-on-one human resource intensive treatment that can only be provided in specialized centers to a technology-driven, remotely-supervised and widely accessible enterprise (Moulaei et al, 2022 ). Given the increased costs associated with long-term rehabilitation and the difficulty in providing appropriate duration and intensity of rehabilitation services required to manage disability, cost-effective development of robotic rehabilitation is greatly warranted.…”
Section: Introductionmentioning
confidence: 99%